(untitled) (Historia, 2021)
It is the main intent of this article to correct a misunderstanding of what engagement in historical studies, historiography and historical culture means and what it is about. So, first of all I will shortly describe the widespread notion of engagement as the direct opposite of objectivity in historical studies. In a second step I will show that this juxtaposition contradicts basic principles of historical thinking. For this I will explicate these principles in a twofold way: first, as basic factors of human historical thinking in general, and, second as basic factors of the professional academic treatment of history. Since historical thinking is more than only a cognitive procedure but includes non-cognitive elements, I will identify these elements and clarify their role as determining factors in historical culture. Doing so, engagement becomes visible as a complex interrelationship of different dimensions of historical culture and their basic concepts. As a further step I will discuss the contribution of historical studies to the practical functions of historical culture in human life. To round off the discussion, I will give a short outlook focusing on a form of engagement which has mainly been overlooked and is worth taking into account. Die hoofdoelwit van hierdie artikel is om die misverstand reg te stel wat betrokkenheid in historiese studies, historiografie en historiese kultuur beteken en waaroor dit opsluit gaan. In ’n tweede stap wil ek aandui dat hierdie jukstaposisie strydig is met sekere basiese beginsels van historiese denke. Daaropvolgend verduidelik ek genoemde beginsels op twee maniere: eerstens as basiese faktore van historiese denke in die algemeen; en tweedens as basiese faktore van die professionele wyse waarop geskiedenis benader word. Omdat historiese denke meer verteenwoordig as bloot kognitiewe prosedures, en in werklikheid ook niekognitiewe elemente bevat, sal ek die elemente verduidelik as bepalende faktore in geskiedskultuur. Daardeur word betrokkenheid sigbaar as a komplekse interaktiewe verhouding met verskillende dimensies van historiese kultuur in die menslike lewe. Teen die einde van die bespreking word ’n kort indruk gegee van ’n vorm van betrokkenheid wat grootliks oor die hoof gesien is, en verdien om in ag geneem te word.